171 - ANALYSIS OF MOTOR DEVELOPMENT IN SCHOOL OF SEVEN YEARS OF AGE: A COMPARATIVE STUDY (Fiep Bulletin - online, 2011)
The aim of this study was to diagnose changes psychomotor children of both sexes, aged 7 years enrolled in two different schools of the network of municipal education located in the city of Manaus. We evaluated 62 children from school A, with 37 girls and 25 boys and 63 from school B, 34 girls and 29 boys. All subjects were assessed by TGMD (Test of Gross Motor Development, Ulrich, 1985) which assesses the motor performance of motor skills of locomotion and object control. The data were presented by descriptive analysis, mean and standard deviation. The data showed a normal distribution we used Student's T test for independent samples to compare genders, for non-normal distribution the Krumam Wallis test, significance level p
Keywords: Fundamental motor skills; Gender; Performance engine